THE EFFECT OF APPLYING PROCESS AND PRODUCT APPROACHES ON THE STUDENTS’ COMPETENCY IN WRITING DESCRIPTIVE TEXT - Yayuk Hayulina Manurung; Rini Rahmadhani Nasution (UIN Sumatera Utara, 2019)
This research was carried due to the fact the students’ skill in expressing the ideas in writing was still the major challenge. Writing had a less attention than other skills where it tends to be as a homework and the teacher did not put too much focus on it since it would not be tested in national exam. The objective of this research was to investigate the effect of applying process and product approaches on the students’ competency in writing descriptive text. This research was conducted at MTs.Islamiyah Medan, JalanSuluh No. 71 D Kec. Medan Tembung. The population of this research was the eighth grade students of the academic year 2017/2018. The sample consisted of 62 students taken by using cluster random sampling technique. The experimental group was consisting of 30 students taught by applying process approach and the control group consisted of 32 students by using lecturing method. Written test was used as the instrument. Each group was given a pre-test, treatment and post-test. The result of this research showed that t-test (17.36) was higher than t-table (2.00) and degree of freedom (df) was 60. The finalhypothesis showed that Ho was rejected and Ha was accepted. It means that there was a significant effect of applying process and product approaches on the students’ competency in writing descriptive text.